Childhood Trauma Associated White Matter Abnormalities in First-Episode Schizophrenia. (1st June 2018) - Asmal, Laila; Kilian, Sanja; du Plessis, Stefan; Scheffler, Frederika; Chiliza, Bonginkosi; Fouche, Jean-Paul; Seedat, Soraya; Dazzan, Paola; Emsley, Robin
Abstract: Schizophrenia is associated with brain connection irregularities within and between brain regions. Childhood trauma increases the risk of schizophrenia suggesting that the relationships between childhood trauma and brain connectivity requires further investigation. Here, we examine the relationship between childhood trauma (as measured by the Childhood Trauma Questionnaire) and fractional anisotropy (FA) in 54 minimally treated first-episode schizophrenia (FES) patients and 51 community matched controls. Patients who experienced high levels of trauma had significantly lower FA in the inferior longitudinal fasciculus (ILF), superior longitudinal fasciculus (SLF), and inferior fronto-occipital fasciculus (IFOF) compared with controls who experienced high levels of childhood trauma. A history of childhood sexual abuse in patients was associated with lower FA in the IFOF, ILF, SLF, and forceps major compared with patients without a history of sexual abuse. However, patients who had experienced childhood emotional neglect had higher FA in the right SLF compared to patients with low levels of emotional neglect. Our findings highlight altered cortico-limbic circuitry in FES patients compared with controls and differential effects of childhood emotional neglect and sexual abuse on white matter in patients. Although stress-related white matter (WM) pathways appear to be involved in both schizophrenia and otherwise healthy controls previously exposed to childhood trauma, the pattern of disruption of WM integrity in FES patients appears to be distinct.